Learning Resources of Bivalves Diversity in the Coastal Intertidal Zone of Biodiversity Materials for the 10th Grade Senior High School: a Literature Study - Rafika Rakhmah; Yahya Hanafi; Destri Ratna Ma'rifah (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
Utilizing the environment as the learning resource can enhance learning activities, but on biodiversity material, teachers have not been able to apply this system on teaching and learning activities. This study aims to determine the level of diversity of Bivalves in the intertidal zone and to analyze the requirements of learning resources. The type of this study is a literature study, which is designed in a narrative review. The data analysis technique used descriptive analysis. The results showed that the Bivalve diversity index belonged to different categories, namely low, medium to high. Based on the analysis of the requirements for learning resources for biology, the results of the study have met the requirements as a source for learning Biology in class X on biodiversity material.